Tooth eruption : an emerging enigma - Orams Hector J. (Sciendo, 1988)
Tooth eruption is a genetically controlled but little understood event. Standard practice has been to divide it into three phases, (1) pre-eruptive. (2) prefunctional and (3) functional. More recently from an orthodontic point of view a six stage division, three stages prefunctional for individual tooth movement and three stages post functional for the whole dentition has been found more useful for clinical purposes.